PENGARUH PENGGUNAAAN TEKNIK PEMODELAN TERHADAP KETERAMPILAN MENULIS TEKS DRAMA SISWA KELAS XI SMA NEGERI 7 PADANG - Andria Catri Thamsin, Mutia Riana, Atmazaki, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this research is to analyze the effect of the use modeling techniques to ward studentsâ€™ writingskill on drama text class XI students of SMA Negeri 7 Padang. The research is quantitative research with experiment method. The design of this research is One Group Pretest-Postest Design. The instrument used is performance test. The data of this research is the score of writing skill test result. Data are collected through performance tests. Based on the result of research, the use of modeling techniques affected the writing skill on drama text class XI of student SMA Negeri 7 Padang.Kata kunci: pengaruh, teknik, menulis teks dramaÂ